1998
DOI: 10.1111/j.1600-051x.1998.tb02424.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and microbiological features of refractory periodontitis subjects

Abstract: The purpose of this investigation was to compare the clinical parameters and the site prevalence and levels of 40 subgingival species in successfully treated and refractory periodontitis subjects. 94 subjects received scaling and root planing and if needed, periodontal surgery and systemically administered tetracycline. 28 refractory subjects showed mean full mouth attachment loss and/or > 3 sites showing attachment loss > 2.5 mm within 1 year post-therapy. 66 successfully treated subjects showed mean attachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
161
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(172 citation statements)
references
References 54 publications
(15 reference statements)
11
161
0
Order By: Relevance
“…in the subgingival microbiota of periodontitis patients in the Dominican Republic, whereas Ali and co-workers (2) observed a frequency of 61.1% of enterics in the subgingival microbiota of periodontitis subjects from Romania. The species P. aeruginosa and A. baumannii, important etiologic agents of nosocomial infections, have been associated with refractory periodontitis, probably due to their elevated resistance to mechanical and antimicrobial therapies (4,29,34). Another pathogen related to antimicrobial resistance is E. faecalis.…”
Section: Figurementioning
confidence: 99%
“…in the subgingival microbiota of periodontitis patients in the Dominican Republic, whereas Ali and co-workers (2) observed a frequency of 61.1% of enterics in the subgingival microbiota of periodontitis subjects from Romania. The species P. aeruginosa and A. baumannii, important etiologic agents of nosocomial infections, have been associated with refractory periodontitis, probably due to their elevated resistance to mechanical and antimicrobial therapies (4,29,34). Another pathogen related to antimicrobial resistance is E. faecalis.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have also observed some association of the bacterial species E. faecalis 19 , S. warneri 14,[19][20][21][22] , and S. aureus [23][24] with periodontal diseases. Furthermore, a recent systematic review by our research group 10 that evaluated the weight of evidence of the existence of new periodontal pathogens suggested that 32 new strains might be associated with the etiology of periodontal diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas, S. warneri was identified by means of genetic sequencing in individuals who did not respond well to periodontal therapy (previously called "refractory periodontitis") 21 . Contrary to other types of staphylococcus, S. warneri has been found in elevated quantities in implants in function for 10 years and showed positive correlation with peri-implant inflammation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The better clinical and microbiological effects observed with the combination of SRP and CHX in this study might be attributed to a beneficial effect of CHX rinsing on subgingival microbial recolonization. Maintaining low levels of supragingival plaque and disturbing periodontal pathogen reservoirs that are not reached by SRP, such as tonsils, tongue, saliva and oral mucous membranes, [29,30] could have a positive influence on recolonization of the recently scaled pockets. It can be concluded from the results of the present study that the treatment with SRP and CHX improved clinical and microbiological parameters compared to the SRP alone as a monotherapy.…”
Section: Discussionmentioning
confidence: 99%